2021
DOI: 10.3390/jcm10215202
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Early Pre-Symptomatic Detection of Influenza Using Continuous Monitoring of Advanced Physiological Parameters during a Randomized Controlled Trial

Abstract: Early detection of influenza may improve responses against outbreaks. This study was part of a clinical study assessing the efficacy of a novel influenza vaccine, aiming to discover distinct, highly predictive patterns of pre-symptomatic illness based on changes in advanced physiological parameters using a novel wearable sensor. Participants were frequently monitored 24 h before and for nine days after the influenza challenge. Viral load was measured daily, and self-reported symptoms were collected twice a day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Furthermore, ultrasound stimulation did not result in further reduction of these circulating cytokines from this low baseline level in ultrasound ( Figure 3B ) or sham-treated cohorts ( Figure 3C ) . Methods of presymptomatic or asymptomatic identification of infection in the absence of detectable changes in systemic markers, such as cytokines, is an active area of research and desirable to aid in infectious disease monitoring and control ( 54 , 55 ). Circulating concentration of the chemokine KC/GRO (i.e., rodent equivalent of CXCL1; a neutrophil chemokine) was elevated 4-hours post-infection, further elevated at 16-hours, and returned towards baseline (i.e., levels measured in the no bacteria controls) at 48 hours following infection ( Figure 3D ) .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, ultrasound stimulation did not result in further reduction of these circulating cytokines from this low baseline level in ultrasound ( Figure 3B ) or sham-treated cohorts ( Figure 3C ) . Methods of presymptomatic or asymptomatic identification of infection in the absence of detectable changes in systemic markers, such as cytokines, is an active area of research and desirable to aid in infectious disease monitoring and control ( 54 , 55 ). Circulating concentration of the chemokine KC/GRO (i.e., rodent equivalent of CXCL1; a neutrophil chemokine) was elevated 4-hours post-infection, further elevated at 16-hours, and returned towards baseline (i.e., levels measured in the no bacteria controls) at 48 hours following infection ( Figure 3D ) .…”
Section: Resultsmentioning
confidence: 99%
“…However, it seems that by further improving these EWS systems, sensitivity could be kept high, while specificity would be higher. This was not achieved yet, but preliminary data from various studies implementing big data analysis of multiple physiologic parameters collected automatically and frequently already show promise in early detection of clinically significant changes, and this could eventually result in the desired combination for future EWSs [24,31].…”
Section: Principal Findingsmentioning
confidence: 99%
“…Activity and physiological trackers are increasingly used globally to monitor an individual's health through continuous or frequent measurement of body functions (physiology) such as heart rate, heart rate variability (HRV), skin temperature, peripheral capillary oxygen saturation (SpO 2 ), physical activity, and indices of sleep quality. Evidence suggests that use of wearable biosensor technology may permit detection of VRTIs, and assist in medical diagnosis in the early stages of disease development - even before the onset of clinical symptoms [ [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] ] - or in state-level real-time surveillance of influenza [ 20 ]. Both of these capabilities are vital to enact timely outbreak response measures and to halt or minimize ongoing transmission.…”
Section: Background and Rationalementioning
confidence: 99%
“…Both of these capabilities are vital to enact timely outbreak response measures and to halt or minimize ongoing transmission. Despite promising results, previous studies of wearables for early detection of VRTIs have been mostly based on biometric data from consumer grade wearables, meaning data collection has been mostly limited to heart rate, HRV, and body temperature [ [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] ]. Prior studies have also relied heavily on patient reported symptoms and could not address asymptomatic or minimally symptomatic infections [ [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] ].…”
Section: Background and Rationalementioning
confidence: 99%
See 1 more Smart Citation